A normative survey of the instruction in health and science in the public elementary schools of Pangasinan - Caronongan, Arturo M. (1960)
This study focused on the instruction of Health and Science in the public elementary schools of Pangasinan for the purpose of proposing measures for improvement.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Health education -- Philippines -- Pangasinan; Science -- Study and teaching (Elementary).